2020
DOI: 10.11604/pamj.supp.2020.35.2.24345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of burnout among primary teachers in confinement during the COVID-19 period in Morocco: case of the Kenitra

Abstract: Introduction Confinement, because of the COVID-19 pandemic, could have problems on the mental health of the population. Teachers responsible for giving distance courses during this period could be psychologically stressed. The aim is to assess the magnitude results of burnout and associated factors among primary school teachers in Kenitra in Morocco during this confinement period. Methods This is a cross-sectional study, which was conducted during the two months of Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 10 publications
2
42
1
5
Order By: Relevance
“…The items are graded on a 7-point Likert scale ranging from 0 (never) to 6 (daily) based on how often one experiences these feelings. The Cronbach's alpha coefficient (α) that tested the internal consistency of the three subscales ranged between 0.74 and 0.90, as obtained in the current and previous studies [22,25].…”
Section: Burnoutsupporting
confidence: 55%
“…The items are graded on a 7-point Likert scale ranging from 0 (never) to 6 (daily) based on how often one experiences these feelings. The Cronbach's alpha coefficient (α) that tested the internal consistency of the three subscales ranged between 0.74 and 0.90, as obtained in the current and previous studies [22,25].…”
Section: Burnoutsupporting
confidence: 55%
“… 24 , 25 These studies suggested that the prevalence of burnout is increasing as a result of the pandemic. Previous studies have also reported burnout as a serious problem in the COVID‐19 pandemic among non‐HCWs, such as teachers, 26 security forces, 27 and managers. Although HCWs are often reported to have a higher psychological burden than non‐HCWs, 28 , 29 the number of patients with COVD‐19 in each region, the timing of the survey, and the type of the questionnaire and cut‐off point of the scale differ among studies.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the workload, many studies have shown that workload (expressed in our study as long hours spent for preparation of materials to be delivered to the students and teaching preparatory students, who are at the beginning of the teen age and need more time to understand and do better job in studying) was closely related to burnout in the form of emotional exhaustion and depersonalization among teachers, including Saudi teachers (Santana et al, 2012;Chalghaf et al, 2019;Amri et al, 2020;Salvagioni et al, 2020;Cobo-Vazquez et al, 2021;Kalynychenko et al, 2021;Li et al, 2021;Melanda et al, 2021;Ribeiro et al, 2021). Moreover, the notion of burnout as a response to job demands has been supported by both selfreports of experienced stress and more objective assessments of demands, such as the number of students and number of working hours (Maslach, 2001;Perry et al, 2014;Peterson et al, 2019;Hart et al, 2020;Ndongo et al, 2020;Shah et al, 2021).…”
Section: Discussionmentioning
confidence: 71%